Éditorial: Philanthropie et Innovation Sociale - Durand Folco, Jonathan (Philab, 2020)
Éditorial pour introduire notre édition spéciale sur la Philanthropie et Innovation Sociale par Jonathan Durand Folco.

Philanthropy and Innovation - Dodgson, Mark; Gann, David (Philanthropy, Innovation and Entrepreneurship: An Introduction, 2020)
This chapter examines the close relationships between philanthropy and innovation. A case study of philanthropy improving eyesight in Africa is provided. The crucial impact of philanthropy on science and universities is discussed. A case study of how philanthropy fundamentally changed Queensland University is provided. The intimate relationship between philanthropy and the arts is explored. A case study is provided of the impact of philanthropy on a major arts institution. The connections between philanthropy and social and humanitarian innovation is described.
Keywords: Australie; Réservé UdeM